PUBLIC POLICIES FOR PEOPLE ON THE SITUATION: A PUBLIC PROBLEM IN REALITY (REMUNOM, 2024)
Currently, homeless people have become a public problem in the country, since, because they have completely different and diverse characteristics, vices and profiles, they make the process of solving the problem even more difficult. Such obstacles are alarming, and it is up to the government through social actions, prevention campaigns and aid to find solutions to reduce the social impact that this situation has been causing.This work consists of dealing with the public problem, seeking to put on the agenda some issues that are relevant so that society together with the rulers can best solve the social obstacle, which ends up being omitted by a large part of the population and also expose how they are originated. and administered to actions developed by public bodies responsible for maintaining policies aimed at homeless people.In this way, we conclude that the aforementioned social problem has become a global humanitarian issue, since it is much more complex than it seems, also exposing other social problems, such as unemployment, violence, drug addiction, among other issues that have more visibility in our society.